Clinical Practice Patterns in Constrictive Pericarditis Patients With Heart Failure: A Retrospective Cohort Study Using a National Inpatient Database in Japan - Isogai, Toshiaki (Clin Cardiol, 2015)
BACKGROUND: Previous studies on constrictive pericarditis (CP) mainly concerned patients undergoing pericardiectomy. The reported perioperative mortality of CP patients remained high. Data on medically treated CP patients without pericardiectomy have been scarce. HYPOTHESIS: Constrictive pericarditis patients with more comorbidities are less likely to undergo pericardiectomy. METHODS: Using the Diagnosis Procedure Combination database from 2007 to 2013, we retrospectively identified CP patients admitted with heart failure of New York Heart Association (NYHA) class II to IV. We compared clinical characteristics between patients treated with and without pericardiectomy. A multivariable logistic regression analysis was performed to assess the factors associated with likelihood of undergoing pericardiectomy. RESULTS: Of 855 eligible patients, 164 (19.2%) underwent pericardiectomy (surgery group) and 691 (80.8%) did not (no‐surgery group). The surgery group was younger (mean age, 65.0 years vs 70.3 years; P < 0.001) and more often male (81.7% vs 72.2%; P = 0.013) than the no‐surgery group. No significant difference was seen in NYHA class and Barthel Index between the groups, whereas the surgery group had a lower Charlson Comorbidity Index (CCI). Older age, female sex, and higher CCI were significantly associated with a lower likelihood of undergoing pericardiectomy. In the surgery group, 30‐day postoperative mortality was significantly higher in patients who underwent cardiopulmonary bypass than in those who did not (11.3% vs 2.9%; P = 0.030). CONCLUSIONS: Patients' backgrounds were associated with the likelihood of undergoing pericardiectomy. Conservative medical therapy may be acceptable in CP patients with severe background and high preoperative need for cardiopulmonary bypass.